Test–retest reliability of four flatwater performance-related tests in canoe slalom athletes - Vajda, Matej; Krupa, Felix; Busta, Jan; Pratt, Jaylene (Frontiers in Physiology, 2023)
This study aims to evaluate the test-retest reliability of four flatwater performance-related tests in canoe slalom athletes.Twenty-two Slovak national team members of junior and U23 age group racing in a category K1 men (K1M), K1 women (K1W) or C1 men (C1M) volunteered to take part in this study. During both test and retest testing sessions athletes performed 4 flatwater tests: SPS -Sprints with a turn to the preferred side (2x15 meters shuttle sprints), SNPS -Sprints with a turn to the non-preferred side (2x15 meters shuttle sprints), SBS -Sprints with turns to both sides (2x 15 meters shuttle sprints) as well as 12x15 AOT -12x15 meters all out shuttle test (12x15 meters shuttle sprints). Each athlete completed two sessions separated by a minimum of 3 days and a maximum of 5 days.The results have shown the excellent test-retest reliability of all four flatwater tests (ICC -SPS: 0.98; SPNPS 0.97; SBS: 0.98 and 12x15m AOT: 0.96). Additionally, results have shown SEM (SPS: 0.14; SPNPS 0.18; SBS: 0.13 and 12x15m AOT: 1.05) and SWC (SPS: 0.21; SPNPS 0.26; SBS: 0.19 and 12x15m AOT: 1.58).Based on our results we suggest that coaches use these valid and reliable tests to assess changes in their athletes' performance-related physical fitness over time, to verify the effectiveness of training programs focused on improvement in specific physical fitness of athletes as well as to identify asymmetries between the preferred and non-preferred side in canoe slalom athletes.